2022
DOI: 10.1149/1945-7111/ac76e4
|View full text |Cite
|
Sign up to set email alerts
|

Melt Synthesis of Lithium Manganese Iron Phosphate: Part I. Composition, Physical Properties, Structural Analysis, and Charge/Discharge Cycling

Abstract: Melt synthesis is a fast and simple process to make dense LiMnyFe1-yPO4 (LMFP with 0 ≤ y ≤ 1) from all-dry, low-cost precursors with zero waste. This study characterizes melt LMFP materials with 0-100% Mn after particle size reduction by planetary milling and carbon coating with glucose. The melt LMFP samples show higher electrical conductivity at similar pellet density than LFP (0% Mn) and LMFP (79% Mn) reference samples made by traditional methods. The melt LMFP samples exhibit higher crystallinity than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…13 An additional 4.2 V hold after formation does not have a strong influence on the initial capacities (see Fig. 3b-1), since LFP has no capacity beyond 3.65 V. 16,17 CTRL cells show high reversible losses even at T S = 40 °C (see Fig. 3a-1).…”
Section: Resultsmentioning
confidence: 98%
“…13 An additional 4.2 V hold after formation does not have a strong influence on the initial capacities (see Fig. 3b-1), since LFP has no capacity beyond 3.65 V. 16,17 CTRL cells show high reversible losses even at T S = 40 °C (see Fig. 3a-1).…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, the production cost of LMFP is relatively low, making it more competitive in the market. 27,28 LiFe x Mn 1−x PO 4 and LiMnPO 4 are two common cathode materials for lithium-ion batteries, and they exhibit significant differences in chemical composition and structure, leading to distinct electrochemical performance and application characteristics. 29 First, in terms of chemical composition, LiFe x Mn 1−x PO 4 contains iron, while LiMnPO 4 primarily consists of manganese.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of environmental friendliness, LMFP is relatively eco-friendly as it does not contain harmful heavy metal elements like nickel and cobalt, reducing its negative impact on the environment. Moreover, the production cost of LMFP is relatively low, making it more competitive in the market. , …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, LFP particles need to be very small to account for low Li diffusivity, further limiting the volumetric energy density. 3 Additionally, LFP has a low crystallographic density, 3.5 g/cc, 4 compared to NMC, 4.8 g/cc, 5 further lowering the energy density. A proposed alternative to LFP is LiMn x Fe 1−x PO 4 (LMFP).…”
mentioning
confidence: 99%
“…Unfortunately, the electrochemical performance of LMFP is inferior to other positive electrode materials, due to poor Li diffusion caused by lattice distortion from Jahn-Teller active Mn 3+ , [8][9][10] in addition to rapid capacity fade compared to LFP. 4 It has been shown that the dominant failure mechanism for Li-ion batteries containing LFP is Li inventory loss due to parasitic reactions damaging the solid-electrolyte interface (SEI) at the negative electrode, where Li is consumed to repair the damage. [11][12][13] Additionally, it has been shown that Mn deposition on the negative electrode can amplify SEI degradation, [14][15][16] which would then increase Li inventory loss in LMFP full cells.…”
mentioning
confidence: 99%